Stories that Make History : The Experience and Memories of the Japanese Military ›Comfort Girls-Women‹ - Son, Angella; The Research Team of the War; Women's Human Rights Center (Genocide and Mass Violence in the Age of Extremes, 2020)
What would it be like if your existence was erased for half a century? This is the reality for the Korean comfort girls-women whose lives had been erased since the time of the expansion of comfort stations by the Japanese military in 1937. This book is an effort to bring these women back to life and to make their voices, experiences and memories available to future generations. The experiences of Korean comfort girls-women are a paradigmatic example of how military sexual violence can obliterate the dignity of women and shame them into nonexistence. This book examines how the turning of their innocence into inadequacy, actively by the Japanese government and passively by the Korean government and its people, and also by the world, compounded their long, miserable suffering for half a century until Kim Hak-sun broke the silence in 1991 with the support of Korean activists. The relentless and courageous efforts of Korean comfort girls-women and activists on the road to healing and justice are shared here. These efforts made it possible for us to hear their horrific stories, which are embedded with numerous and intense traumas, allowing them to unfold and be shared on the road to justice and healing.